Improving Students’ Speaking Skill Through TPR (Total Physical Response) Technique on Command at Second Semester of STIE-SAK Academic Year 2022/2023 - Kartawijaya, Sukarta; Padli, Al; Yelnim, Yelnim (Universitas Pahlawan Tuanku Tambusai, 2023)
The form of this research is classroom action research. The purpose of this research is to know the students’ speaking skill at second semester of STIE-SAK academic year 2022/2023 through TPR (Total Physical Response) technique and to explain the factors influence students’ speaking skill. This research will be done in four phases namely planning, acting, observing and reflecting. This research is done in spiral cycle, there are two cycles in this research. This research is done in STIE-SAK. Speaking isan important part of language, and it is important to be mastered. A we know that, speaking cannot be learned without practice and practice it. It means that to master speaking, student have to speak. So as a teacher, we have to give more activities for the students in the class to use the language by using various ways in teaching.However, based on the researcher’s observation and experiences in teaching English at second semester students of STIE-SAK, there are only a few students who got good score and most of them got low score in speaking English. It meant that there are some problems faced by the students. First, the students’ speaking skill is low. The students do not understand the command from the teacher such as “listen to me, open your book, stand up, etc”. Second, the students are shy to speak in the class, the students mostly kept silent when their lecturer asks them to do something or to say a word in English. Third, they also havea limited vocabulary so they do not understand the instructions given by the lecturer. To solve the problems, it needed an implementation of appropriate model in teaching. There are many techniques that could be used in teaching and learning. One of them was Total Physical Response (TPR). Total physical response is a language teaching built around the coordination of speech and action. It meant that there are speech and action on it. The reason to choose TPR because it can improve the students’ vocabulary, the students uses TPR in speaking and the topic used is based on the syllabus.